Application of Sustainable Integrated Process Design and Control for Four Distillation Column Systems - Mohamad Z., Nordin; Mohamad R., Othman; Mohd K. A., Hamid (AIDIC Servizi, 2015)
The objective of this paper is to present the application of sustainable integrated process design and control methodology for distillation columns systems. The sustainable integrated process design and control methodology is developed and able to find the optimal solution for a single distillation column to ensure the design is more cost efficient, controllable and sustainable to meet the product quality. The sustainable integrated process design and control problem for a distillation column system is typically formulated as a mathematical programming (optimization with constraints) problem, and solved by decomposing it to six sequential hierarchical sub-problems: (i) pre-analysis, (ii) design analysis, (iii) controller design analysis, (iv) sustainability analysis, (v) detailed economics analysis and (vi) final selection and verification. In the pre-analysis sub-problem, the concept of driving force is used to locate the optimal design-control-sustainable solution targets, which are defined at the maximum point of the driving force diagram. The sustainability analysis sub-problem was analysed by using the threedimensional sustainability index. The results through separation of n-Pentane, n-Hexane, n-Heptane, nOctane and n-Decane mixtures with four distillation column systems shows the methodology is capable to find the optimal solution for multiple distillation column systems that satisfies design, control and sustainability criteria in a simple and efficient way